Застосування мережевого рольового аналізу для побудови та оцінки трофічних мереж пасторальних екосистем - Руденко, С.С.; Буждиган, О.Я. (Видавничий дім "Академперіодика" НАН України, 2008)
A methodological base for using the network role analysis for the building and estimation of trophic networks of pasture ecosystems is developed. General theoretical principles of the structure and performance of the trophic networks of pastures are discovered.